Kinetics and the Effect of Refining Methods on the Physicochemical Properties, Fat Soluble Vitamins and Nutritional Metal Content of Hura crepitans Oil: Refining Effects on Hura crepitans Oil (Biological Sciences - PJSIR, 2009)
The effect of three refining methods, viz. alkali refining, degumming and bleaching was investigated on the physicochemical properties, fat soluble vitamins and nutritional metal content of Hura crepitans oil. The processes increased the glyceride content while there was reduction in the nutritional metal content of the oil. The effect of temperature (60-180 °C) and time (upto 90 min) was also considered using the bleaching method with surface active clay and activated charcoal. The adsorption of peroxides was adequately modeled by Arrhenius type of equation and described by the first-order kinetic. The activation energy for bleaching at 120 °C and 45 min was 244.60 cal/mole. Among all the refining methods, bleaching appeared to be the best technique for refining in terms of stability and improvement of physicochemical properties of the H. crepitans seed oil.